In vitro allelopathic effects of extracts and amenthoflavone from Byrsonima crassa (Malpighiaceae) - Rolim de Almeida, Luiz Fernando [UNESP]; Sannomiya, Miriam [UNESP]; Rodrigues, Clenilson M. [UNESP]; Delachiave, Maria Elena [UNESP]; Dos Santos, Lourdes Campaner [UNESP]; Vilegas, Wagner [UNESP]; De Feo, Vincenzo (Taylor & Francis Ltd, 2007)
Extracts and pure amenthoflavone isolated from Byrsonima crassa (Malpighiaceae), a shrub growing in the semi-arid region of Brazil Cerrado, were evaluated in vitro, at different doses, for their effects on tomato seed germination and subsequent growth of seedlings. A hydromethanolic extract showed general stimulatory effects. The EtOAc extract stimulated root elongation and root weight of tomato; shoot elongation was inhibited, while shoot weight was not altered. The pure amenthoflavone isolated from the plant, stimulated shoot elongation at concentrations ranging between 10(-4) M and 10(-6) M.
Keywords: Byrsonima crassa; amenthoflavone; tomato seeds; germination; shoot weight and elongation; root weight and elongation